Emotional competences as predictors of psychological wellbeing and quality of life of supplementary grandparents caregivers - Galarraga, Leyre; Noriega, Cristina; Pérez-Rojo, Gema; López, Javier (Frontiers in Psychology, 2024)
Introduction. Grandparents are increasingly becoming key figures in the supplementary care of grandchildren. Based on the Resilience Model of Family Stress, Adjustment and Adaptation, the present study aims to analyze the emotional competences that can predict higher levels of psychological wellbeing and quality of life in supplementary grandparents caregivers.Methods. A sample of 270 supplementary grandparents caregivers living in Spain participated. Most participants were women (71.1%), and the mean age was 67.83 years (SD = 6.26). Most participants were occasional caregivers, that is, they care for less than 10 hours per week (76.3%). We conducted multiple linear regression analyses, one for psychological wellbeing and the other for quality of life.Results. The regression model for psychological wellbeing identified that age, management of caregiving stress, self-confidence in the caregiving role, management of work-life balance difficulties and emotional self-regulation explained 31.5% of its variance. The regression model for quality of life showed that age, management of caregiving stress, work-life balance difficulties, emotional selfregulation, type of grandparent caregiver and grandparenting role meaning explained 28.9% of its variance.Conclusions. This study focuses on supplementary grandparent caregivers, whereas literature has tended to look at primary grandparent caregivers. The results highlight the role of emotional competences as predictors of supplementary grandparents caregivers' psychological wellbeing and quality of life, overcoming the usual tendency in the literature to focus on the negative consequences of grandparent caregiving for grandchildren, and emphasizing the competences that grandparents have to cope with this care in a satisfactory way, which, moreover, can be trained.